Effects of anterior hypothalamic disconnection on the evolution of goldblatt renal hypertension: A dual response - Castro, Almir L. [UNESP]; Almeida, Eloisa F. [UNESP]; Vadenal, Ricardo [UNESP]; Lopes, Oswaldo U. [UNESP] (Wolters Kluwer, 1983)
The role of the central nervous system, in general, and of the hypothalamus, in particular, in the genesis of various forms of experimental hypertension has been the object of increased investigation. Lesions of the dnteroventral area of the third ventricle (AV3V) in rats seem to block the development of various forms of hypertension. In the present experiments, AV3V was kept intact but its connections with the caudal neuroaxis were.severed by means of a curved knife (2 mm radius), stereotaxically placed at the level of the arcuate nucleus. This disconnection, per se, induces poh/dipsia, and a reduction of the pressor effect of i.v.-infused angiotensin II. The interactions of simultaneously performed hypothalamic disconnection (HD) and Goldblatt one-kidney, one clip, (1K1C) or two-kidney, one clip (2K1C) hypertensions was studied. It was found that HD retards and attenuates the development of 1K1C hypertension but does not materially affect the evolution of the 2K1C model. Rats with established 1K1C or 2K1C hypertensions were not affected by HD, whereas rats with chronic HD (4 weeks) showed slight and slow developing hypertension in response to clipping. The possible significance of these results with respect to the neural connections of AV3V is discussed. © 1983 American Heart Association, Inc.
Keywords: Brain disconnection; Central nervous system; Hypertension; Hypothalamus angiotensin II